PRESEPSI AUDITOR DAN USERS TERHADAP LAPORAN AUDIT DAN LAPORAN REVIEW - MF.ARROZI ADHIKARA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2003)
The main focus of this studi to examine the extent of audit and review expectation gap in existence in Indonesia by primally considering the differences between the expectations users of audited and review financial reports with auditor’s perceptions of their role about responsibility, reliability, and decisions usefulness. That is the reasonableness aspect of gap. Analysis were based on 278 respondens in three cluster sampling were auditor, investor, and management. Hipotesis testing used Mann-Whitney test to knew expectation gap auditor with users were investor and management. The result found evidence of a wide expectation gap in Indonesia in the first areas of auditor responsibility for auditor is responsible for detecting all fraud, auditor is not responsible for preventing fraud, and auditor doesn’t exercise judgement in the selection of review/audit procedures. Second, the areas of statement reliability for users have absolute assurance that financial statement contain no material misstatements, auditor doesn’t agree with accounting policies used in the financial statements, the financial statements give a true and fair view. Third, the areas of statement decision usefulness for audited/reviewed financial statement are not useful for making decisions. The result strongly support improving decision making by financial statement users. This result had shown expectation gap between auditor with investor and management in Indonesia.